A Nonrandomized Comparison Study of Self-Hypnosis, Yoga, and Cognitive-Behavioral Therapy to Reduce Emotional Distress in Breast Cancer Patients. Issue 2 (3rd April 2017) - Bragard, Isabelle; Etienne, Anne-Marie; Faymonville, Marie-Elisabeth; Coucke, Philippe; Lifrange, Eric; Schroeder, Hélène; Wagener, Aurélie; Dupuis, Gilles; Jerusalem, Guy
Abstract: The authors asked breast cancer (BC) patients to participate in 1 of 3 mind-body interventions (cognitive-behavioral therapy (CBT), yoga, or self-hypnosis) to explore their feasibility, ease of compliance, and impact on the participants' distress, quality of life (QoL), sleep, and mental adjustment. Ninety-nine patients completed an intervention (CBT: n  = 10; yoga: n  = 21; and self-hypnosis: n  = 68). Results showed high feasibility and high compliance. After the interventions, there was no significant effect in the CBT group but significant positive effects on distress in the yoga and self-hypnosis groups, and, also, on QoL, sleep, and mental adjustment in the self-hypnosis group. In conclusion, mind–body interventions can decrease distress in BC patients, but RCTs are needed to confirm these findings.